Exercise during pregnancy improves maternal glucose screen at 24–28 weeks: a randomised controlled trial. Issue 9 (26th September 2011) - Barakat, Ruben; Cordero, Yaiza; Coteron, Javier; Luaces, Maria; Montejo, Rocio
Abstract : Objective: The influence of an exercise programme performed by healthy pregnant women on maternal glucose tolerance was studied. Study design: A physical activity (PA, land/aquatic activities) programme during the entire pregnancy (three sessions per week) was conducted by a qualified instructor. 83 healthy pregnant women were randomly assigned to either an exercise group (EG, n=40) or a control (CG, n=43) group. 50 g maternal glucose screen (MGS), maternal weight gain and several pregnancy outcomes were recorded. Results: Significant differences were found between study groups on the 50 g MGS. Values corresponding to the EG (103.8±20.4 mg/dl) were better than those of the CG (126.9±29.5 mg/dl), p=0.000. In addition, no differences in maternal weight gain and no cases of gestational diabetes in EG versus 3 in CG (7%) (p>0.05) were found. Conclusion: A moderate PA programme performed during pregnancy improves levels of maternal glucose tolerance.